Sudan : Public Expenditure Review, Synthesis Report - World Bank (Washington, DC, 2012)
This synthesis provides a baseline assessment of two fundamental dimensions of public finance in post-CPA Sudan-fiscal management and the alignment of resources to broad-based growth and reduced poverty and inequality. This Public Expenditure Review (PER), the first for Sudan, reflects the initial phase of engagement, with the objective of identifying and supporting improvements in budget planning, monitoring and institutional arrangements so as to contribute to improved resource use and outcomes. The emphasis is on establishing a baseline understanding of key fiscal management and policy challenges, highlighting reform measures for policymakers, and setting the agenda for the next phase of work. This report begins with an introduction. The rest of the synthesis report is structured as follows. Sections 2 and 3 cover the Government of National Unity (GNU) revenue and expenditure management, respectively. Section 4 summarizes key aspects of the PER dialogue on identifying and monitoring pro-poor spending in Sudan. Intergovernmental transfers and fiscal decentralization are the focus of Section 5, and section 6 summarizes the main findings from the PER state case studies. Section 7 is dedicated to fiscal issues in the South.